2018
DOI: 10.5535/arm.2018.42.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Therapy of Robot and Low-Frequency Repetitive Transcranial Magnetic Stimulation on Hemispatial Neglect in Stroke Patients

Abstract: ObjectiveTo investigate the effect of upper limb rehabilitation combining robot with low-frequency repetitive transcranial magnetic stimulation (rTMS) on unilateral spatial neglect in stroke patients.MethodsPatients who had hemispatial neglect after right hemisphere stroke were randomly divided into rTMS only group, robot only group, and combined group. All groups received conventional neglect therapy and additional treatment for each group. rTMS group received rTMS therapy. Robot group received robot therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…On the other hand, only the cTBS group showed significant increase in fractional anisotropy (FA) and mean diffusivity (MD) in superior longitudinal fasciculus, superior occipitofrontal fascicle and inferior fronto-occipital fasciculus on the left side (stimulation side) and the capsula external and inferior fronto-occipital fasciculus on the right side (contra-stimulation side). In a study by Kim et al 25 using both robotic therapy and rTMS, significant improvements were observed in all groups, but there were no significant differences between the groups.…”
Section: Treatment Characteristics Outcomes and Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, only the cTBS group showed significant increase in fractional anisotropy (FA) and mean diffusivity (MD) in superior longitudinal fasciculus, superior occipitofrontal fascicle and inferior fronto-occipital fasciculus on the left side (stimulation side) and the capsula external and inferior fronto-occipital fasciculus on the right side (contra-stimulation side). In a study by Kim et al 25 using both robotic therapy and rTMS, significant improvements were observed in all groups, but there were no significant differences between the groups.…”
Section: Treatment Characteristics Outcomes and Resultsmentioning
confidence: 87%
“…In terms of the impairment assessed, eight articles reported on global cognition and seven on USN. Kim et al 25 compared rTMS alone, robot rehabilitation, and combination therapy. In terms of the stimulation pattern, five articles of rTMS study used inhibition stimulation pattern.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 630 studies were identified, and after reading the titles and abstracts, 23 studies were selected for eligibility analysis, 18 of which were excluded because they were prospective studies ( n = 2), case series ( n = 3), proof of concept ( n = 1), did not use any type of robot ( n = 4), did not include USN patients ( n = 5), used robot without limb activation ( n = 1), and were clinical trial protocols ( n = 2). In total, two RCTs, 53,54 two pilot RCTs, 55,56 and one quasi-RCT 57 were included in the qualitative analysis. A flowchart of the review steps is shown in Figures 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the individuals in the experimental and control groups was 60.65 (±8.88) years and 63.41 (±9.13) years, respectively. Three studies included patients in the subacute phase, 53,54,56 one in the chronic phase, 55 and one in the acute phase 57 of stroke. In all studies, the individuals had ischemic and/or hemorrhagic strokes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, given a recent previous study reporting that robot-assisted therapy could be simultaneously provided with repetitive transcranial magnetic stimulation and it was found to be clinically effective, a combination treatment for visual sensory stimulation needs to be investigated rather than an individual treatment to maximize its effects in clinical settings. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%